Narrative, Periphery and Empire: An Understanding of Conrad´s Nostromo - Figueroa, José Antonio (Pontificia Universidad Javeriana, 2014)
This article attempts to demonstrate how Jospeh Conrad´s novel forms part of a vast ensemble of political, aesthetic and ethnographic production that originated with and gave meaning to the differentiation «center-periphery» grounded in the consolidation of imperialism.